Johnny and the dead - Pratchett, Terry; Briggs, Stephen, adap. (Oxford : Oxford University Press, 2003)
Twelve-year-old Johnny Maxwell suddenly starts seeing and talking ghosts; and, along with his friends, becomes involved in a battle to save the local cemetery.
Keywords: Cemeteries -- Plays; Ghosts -- Plays